Tax Avoidance: Peran Ukuran Perusahaan, Leverage, dan Profitability - Stefany Tjung; Khairudin Khairudin (Universitas 17 Agustus 1945, 2024)
Tax evasion can be defined as the activity of avoiding taxes by citizens or entities that are obliged to pay taxes in order to reduce the tax costs that must be paid by utilizing the tax law which has loopholes and weaknesses. This research aims to explain whether company size, leverage and profitability influence tax avoidance or not. The research took 24 samples of manufacturing companies listed on the Indonesian Stock Exchange for the 2017 - 2019 period. The data used was collected through purposive sampling and using panel data regression analysis techniques through one qualitative and six quantitative tests. The final conclusion concludes that company size as the first variable has a positive influence on tax avoidance, so that it means companies with large sizes tend to avoid tax avoidance. The second variable, namely leverage, has the result of having no influence on tax avoidance. Third, profitability has a negative influence on tax avoidance, meaning that companies with large profits will increase the company's tendency to avoid taxes.